Wybory edukacyjno-zawodowe młodzieży gimnazjalnej w kontekście aktualnych potrzeb rynku pracy = Educational and vocational choices of junior high School youth in the context of the actual labour market needs. A report from research - Kozielska, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The text illustrates selected conclusions from a four-module research project conducted in one of Wielkopolska counties, i.e. Gniezno county. The main aim of the article is to present educational and vocational choices of junior high school youth in the context of the situation on the local labour market. The authors reveal weaknesses in vocational counseling and in the condition of vocational education. Attention was also paid to the depreciated in the eyes of society vocational education (since the school year 2017/2018 industry education). Considering labour market realities in counties, such education seems to be a rational choice, not closing the path to universities. Problems of vocational education and discussions over it constitute an additional element of the paper. The topic taken up in this text falls within the scope of social sciences, pedagogy.
Keywords: planowanie przyszłości edukacyjno-zawodowej; doradztwo zawodowe; rynek pracy; młodzież; szkolnictwo zawodowe; planning educational and vocational future; vocational counselling; labour market; youth; vocational education